FRI0428 Mean number of capillaries is associated with disease activity at 6 months follow-up in systemic sclerosis patients. (12th June 2018) - Gheorghiu, A.M.; Oneata, R.; Radu, A.; Briceag, A.; Draganescu, C.; Vranceanu, C.; Magda, S.; Constantinescu, T.; Soare, A.; Dobrota, R.; Ancuta, I.; Ciofu, C.; et al.
Abstract : Background: Nailfold capillaroscopy (NFC) is essential in the evaluation and classification of systemic sclerosis (SSc). The mean number of capillaries is considered a promising tool for assessing vascular involvement in SSc, however there is no consensus yet over how many digits should be analysed and how. Objectives: Investigation of the associations of the mean number of capillaries, measured by NFC with disease activity (EScSG activity score) and vascular involvement (digital ulcers (DUs) or history of DUs) in a single-centre cohort of patients with SSc. Methods: 68 patients with SSc fulfilling the ACR/EULAR 2013 classification criteria were included. NFC and extensive assessment per the recommendations of EUSTAR were performed in all patients. 54 patients had a follow-up (FU) at 6 months. 8 digits were examined (II to V of both hands) by NFC; 4 images for each finger were saved. The NFC images were assessed by two experienced raters independently, scoring the mean number of capillaries in all fingers (m_nr/pat), in the 3rd finger of the dominant hand (m_nr/3rd dom) and in the 4th finger of the non-dominant hand (m_nr/4th non-dom) for each patient. "Early', 'active' and 'late' Cutolo patterns were also recorded. Results: 2176 images were scored at baseline and 1728 at FU. The m_nr/pat at baseline ranged between 3.4–9.1, mean(SD) 5.6 (1.7) for rater 1, respectively 3.3–8.9, 5.2 (1.4) for rater 2. There was good to excellent correlation (Spearman's rho) at baseline and FU of the m_nr/pat with m_nr/3rd dom, m_nr/4th non-dom and Cutolo patterns, and fair correlation of m_nr/3rd dom with m_nr/4th non-dom and Cutolo patterns. We found significant differences of all mean scores of capillaries between patients with and without history of DUs (Mann Whitney U test) (table 1). Using linear regression adjusted for age, gender and history of DUs, mean number of capillaries was associated with disease activity at FU (table 2). Conclusions: The mean number of capillaries had a good association with the history of DUs and predicted disease activity at 6 months follow-up. The m_nr/pat performed better in our analysis than the m_nr/3rd dom and m_nr/4th non-dom, however these could be used alternatively in clinical practice as they are less time consuming. Acknowledgements: This work is part of the QUANTICAP project Disclosure of Interest: None declared